REKONTEKSTUALISASI PENJATUHAN TALAK TIGA DALAM BINGKAI NEGARA INDONESIA - Syaiful Annas (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
This study discusses the law of three divorces in one word or one assembly which often occurs in Muslim societies. The basis used as a reference is the hadith of the Prophet SAW and Fiqh. As a rule of law country, Indonesia has provided rules for the implementation of divorce as stipulated in Law No. 1 of 1974 concerning Marriage, Law No. 7 of 1989 concerning the Religious Courts, and the Compilation of Islamic Law. The substance is that divorce can only be carried out before a court hearing. However, there are still many practices that occur in society imposing triple talaq on a wife in one word or one assembly. This research is library research with a qualitative approach. The results of this study, that the imposition of divorce with one word or in one assembly needs to be reconstructed in understanding hadith and Fiqh as a form of ijtihad with various approaches within the framework of a rule of law that realizes the goals of the law itself.